Psychological abuse is not a problem! Exploring the role of domestic violence myths in psychological revictimization - Cinquegrana, Vincenza; Marini, Maddalena; Galdi, Silvia (Frontiers in Psychology, 2023)
Research provided evidence that IPV myths affect women's acceptance of psychological aggression in intimate relationships, increasing revictimization. However, no study to date has investigated how endorsement of IPV myths leads victims of psychological IPV to accept psychological aggression. In the present study (N = 207 young Italian women involved in heterosexual romantic relationships), we assessed acceptance of IPV myths, prevalence of psychological abuse (in the past 12 months), perception of the problematic nature, and acceptance of psychological aggression in intimate relationships. Results showed that the effect of IPV myths on participants' acceptance of psychological aggression was mediated by the tendency to consider psychological aggression as unproblematic. Notably, this effect was significant only for women who had experienced some form of psychological abuse by an intimate partner in the past 12 months. These findings have relevant implications for prevention strategies about risks of revictimization.